The art of preaching Old Testament poetry - Mathewson, Steven Dale (Baker Academic, a division of Baker Publishing Group, 2024)
"A leading pastor theologian guides readers through preaching the Old Testament poetic books, introducing foundational issues and offering basic methodology and preaching strategies that are faithful to the text and sensitive to its listeners"--